A new approach for operating powered wheelchairs by people with severe impairments - Urbano, Maria Margarida (2009)
This paper discusses the introduction of mechanisms to adapt commercial powered wheelchairs in order to facilitate its driving by people with severe impairments. Several models of operation are proposed and the most promising, at the moment, called legacy adapted mode, is detailed. A part of the formal operation model is presented. The model is then used in the STAGE simulator, not only for its valuation, but also to tune operational parameters that will be specific of each patient and to train the patients without a real wheelchair.